Increasing Women’s Voice and Agency Using Role Models and Skills Training: Experimental Evidence from the MNREGA Program in Odisha, India - Kosec, Katrina; Raghunathan, Kalyani; Kyle, Jordan; Narayanan, Sudha; Karachiwalla, Naureen (AEA RCT Registry, 2023)
Can exposing women to role models improve their participation in community decision-making and broadly increase their perceived voice and agency beyond the household? And can additionally providing skills training on identifying policy priorities, setting goals, and speaking in public bolster any effects? We consider these research questions in the context of the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) program in the eastern Indian state of Odisha. The MGNREGA entitles each rural Indian household to a minimum of 100 days of manual unskilled work at stipulated minimum wages. A key secondary goal of this program is creating durable assets to promote sustainable rural livelihoods. On paper, decisions around which assets will be constructed and where are to be made by community members in a participatory process. Across 94 communities in 4 districts, we will gather 1400 groups of women (approximately 15 per community). Each group will involve a target woman – selected at random from among all women in the community whose households hold an MGNREGA job card (a necessary document to participate in the program and select assets) – as well as 3-5 friends or neighbors (not family members) she invites to join her. Interventions with these groups will be conducted by a team of trained facilitators, one per group.